Light Encryption Scheme Using Light-Emitting Diode and Camera Image Sensor - Yang Liu; Kevin Liang; Hung-Yu Chen; Liang-Yu Wei; Chin-Wei Hsu; Chi-Wai Chow; Chien-Hung Yeh (IEEE Photonics Journal, 2016)
Visible light communication (VLC) is regarded as relatively secure communication when compared with other wireless communications using radio frequency (RF). However, due to the visual nature, the VLC signals are still subject to eavesdropping when they are emitted by the light source. Here, we propose a light encryption scheme using devices having light-emitting diode (LED) and a camera image sensor, such as a mobile phone. The original visible signal sending from the lamp can be first received by the proposed light encrypter. The information can be encrypted and then emitted. The light encrypter acts as an encryption gateway for signals in optical domain. The rolling shutter effect of the complementary metal--oxide semiconductor (CMOS) camera in the mobile phone can be used. By demodulating the rolling shutter pattern, the data information can be obtained. We also propose and demonstrate using the Otsu thresholding scheme to define the data logic in the rolling shutter pattern. We show that the Otsu scheme is effective for estimating the bit error rate (BER). The optimum number of intervals (segmentations) and the process time of the Otsu method are also studied.